2009
DOI: 10.1155/2009/397079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of Spreading Endometrial Cell by Hysteroscopy: A Prospective Longitudinal Study

Abstract: Objective. The aim was to assess the intraperitoneal spread of endometrial cells during hysteroscopy. Study Design. Seventy-six women were submitted to a hysteroscopy with CO2 under a low pressure. Group 1 had not previous diagnosis of endometrial cancer, and group 2 had previous diagnosis of endometrial cancer (stage I-92.3%). Two peritoneal washing samples were taken before (PW1) and immediately after (PW2) the procedure. The dissemination for the peritoneal cavity was defined by the presence of endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Thus, it seems that gas hysteroscopy using pressure below 80 mmHg and carbon dioxide appears to be a safe diagnostic technique in patients with suspected endometrial cancer. Similar data were presented by Cicinelli et al [26] on the basis of a randomized clinical study of a group of 140 women subjected to 5 years' observation after diagnostic hysteroscopy procedure using liquid under pressure lower than 70 mmHg. These authors did not observe intraperitoneal metastasis of endometrial cancer cells in course of the diagnostic procedure and did not find increased risk of relapse of cancer within 5 years of observation [26].…”
Section: The Risk Of Endometrial Cancer Intrabdominal Spread Followinsupporting
confidence: 77%
“…Thus, it seems that gas hysteroscopy using pressure below 80 mmHg and carbon dioxide appears to be a safe diagnostic technique in patients with suspected endometrial cancer. Similar data were presented by Cicinelli et al [26] on the basis of a randomized clinical study of a group of 140 women subjected to 5 years' observation after diagnostic hysteroscopy procedure using liquid under pressure lower than 70 mmHg. These authors did not observe intraperitoneal metastasis of endometrial cancer cells in course of the diagnostic procedure and did not find increased risk of relapse of cancer within 5 years of observation [26].…”
Section: The Risk Of Endometrial Cancer Intrabdominal Spread Followinsupporting
confidence: 77%
“…It is well accepted that the migration of malignant cells during hysteroscopy is possible, but further studies are needed to understand the consequences of the spillage on the prognosis of the disease. Several studies have shown the presence of an increased incidence of peritoneal tumor cells in patients undergoing hysteroscopy; however, the current evidence has not shown that hysteroscopy has an impact on the prognosis of the disease [4,21,[25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 82%
“…The normal saline usage is frequently linked with positive peritoneal cytology (14%) when compared to carbon dioxine (1.4%) (OR = 11.2; 95% CI 1.3-94.5; p = 0.009) [24]. Similarly, hysteroscopic procedures performed with intrauterine pressures below 50 mmHg have no link with an increased frequency of positive peritoneal cytology [26,27]. Unfortunately, in current study, the information on the intrauterine pressure was used during the diagnostic hysteroscopic procedures is missing.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of published studies, the data on the type of medium used during hysteroscopy and its relationship to tumor cell migration into the abdominal cavity are inconclusive. However, there are reports, both showing and denying, that the use of a liquid medium is associated with a higher risk of tumor cell outflow through the Fallopian tubes when compared to carbon dioxide [ 61 ].…”
Section: Hysteroscopy and Laparoscopymentioning
confidence: 99%